The Tanh Method for Kink Solution of Some Modified Nonlinear Equation (Journal of Partial Differential Equations, 2014)
The tanhmethod is a very powerful technique for computation of exact traveling wave, in this paper this method has been employed for specialmodified states of Burger, Klein-Gordon and Fisher-Burger equations and the solitary solution of these equations are derived.